Si-C Coupling Reaction of Hydrosilane with Activated Organic Compounds: A Facile Synthetic Route to Organosilicon Compounds - Yoo, Bok Ryul; Han, Joon Soo (BENTHAM SCIENCE PUBL LTD, 2011)
Hydrosilane undergoes useful and interesting Si-C coupling reactions with activated organic compounds such as linear and cyclic alkyl chlorides, polychloromethanes, terminal and internal alkenes, and linear and cyclic conjugated dienes to give a variety of organosilicon compounds with Si-Cl units: 1) thermal induced and Pt-catalyzed hydrosilylation reaction with unsaturated organic compounds, 2) organic salt-catalyzed dehydrochlorinative Si-C coupling reaction with alkyl chlorides, 3) double silylation with olefin, and silylene-trapped ring closure reaction with conjugated dienes. In the quaternary phosphonium chloride-catalyzed dehydrochlorinative Si-C coupling reactions of activated organic compounds with HSiCl3, the reaction with relatively activated allyl chloride and benzyl chloride proceeded at 130 degrees C to give the corresponding coupling products in good to excellent yields, while that of silylalkyl chlorides and primary/secondary alkyl chlorides required high reaction temperatures of 150 degrees C and 170 degrees C, respectively and long reaction times. Reaction with olefin at the high temperature of 180 degrees C gave double silylation product in good yield. Conjugated dienes reacted with 1a at 150 degrees C to afford 1,1-dichlorosilacyclopent-3-ene. This review is designed to organize the Si-C coupling reactions into categories that illustrate distinct patterns of reactivity. It is hoped that an understanding of such patterns will stimulate the use of Si-C coupling reactions in the synthesis of organosilicon compounds.
Keywords: HIYAMA CROSS-COUPLINGS; CARBOSILANE DENDRIMERS; STABLE SILYLENE; ALKYL-HALIDES; PALLADIUM; HYDROSILYLATION; TRICHLOROSILANE; ALLYLATION; SILYLATION; CHEMISTRY